Perkembangan Konseling Pada Abad 21: Konselor Sebagai Profesi Yang Mengedepankan Tanggung Jawab Kehidupan Efektif Konseli - Kushendar, Kushendar; Maba, Aprezo Pardodi; Zahro, Indah Fajrotuz; Fitri, Hartika Utami (Universitas Muria Kudus, 2018)
Guidance and counseling in Indonesia has been around since the 1970s. Despite all the obstacles in his journey, Guidance and counseling continue to develop. Counselor Profession has taken a role in optimizing the potential of individuals who receive their services. Along with the entry of globalization, the role of the counselor is increasingly central, the problems faced by the counselors are increasingly diverse. Governments through professional organizations have developed a standardized guide to meet the inherent expectations of the Counselor profession. Through this article the author tries to give an overview of the responsibilities that must be met by the counselor in various settings as an effort to maintain and improve the lives of effective counselee.